Pendekatan Pelayanan Kesehatan Holistik-Komprehensif Pada Kasus Menopause - FEBRI ENDRA BUDI SETYAWAN; FENY TUNJUNGSARI; RETNO LESTARI (Universitas Hang Tuah, 2020)
Abstract Menopause is a natural process that occurs in the reproductive cycle of women aged over 40 years. These changes will affect physical and psychological state of a woman, and they are not ready to deal with this condition. Family doctors should provide information about menopause and how to manage various changes during menopause. The results of previous studies were very limited in examining various menopausal management options which were safe, comfortable and have less negative impacts. This study aimed to examine a holistic-comprehensive approach in the case of menopause. Systematic review results were obtained from 55 reference sources through Science Direct, Google Scholar, Proquest Health and Medical Complete, Proquest Nursing and Allied Health Source from 2010 to 2019. The systematic review results explain that the management of menopause cases can be optimized through a holistic-comprehensive approach. Holistic aspect includes the components of biopsychosocial and comprehensive needs which are carried out through promotive, preventive, curative and rehabilitative efforts. Menopausal women often not only experience physical symptoms, but also psychological symptoms which will impact their quality of life. It can be concluded that a holistic-comprehensive approach can be carried out as an effort by family doctors to optimize the management of menopause